2009
DOI: 10.1016/j.jmb.2008.10.078
|View full text |Cite
|
Sign up to set email alerts
|

Cryoelectron Microscopy Structure of Purified γ-Secretase at 12 Å Resolution

Abstract: γ-Secretase, an integral membrane protein complex, catalyzes the intramembrane cleavage of the β-amyloid precursor protein (APP) during the neuronal production of the amyloid β-peptide (Aβ). As such, the protease has emerged as a key target for developing agents to treat and prevent Alzheimer's disease. Existing biochemical studies conflict on the oligomeric assembly state of the protease complex, and its detailed structure is not known. Here, we report that purified active human γ-secretase in digitonin has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
92
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 43 publications
5
92
1
Order By: Relevance
“…Nondenaturating electrophoresis analyses were carried out (blue native PAGE), with HEK293 taken as a reference for the formation of the native ␥-secretase complex (70). MEF ϩ/ϩ and HEK293 cells, but not MEFPSdKO, showed two high molecular mass bands, between 242 and 480 kDa, both positive for PS1 and PS2, compatible with the previously described high molecular mass band (ϳ400 kDa) observed for fully assembled ␥-secretase (45, 70) (Fig.…”
Section: Expression Of Ps1 or Ps2 In Mefpsdko Cellsupporting
confidence: 83%
See 1 more Smart Citation
“…Nondenaturating electrophoresis analyses were carried out (blue native PAGE), with HEK293 taken as a reference for the formation of the native ␥-secretase complex (70). MEF ϩ/ϩ and HEK293 cells, but not MEFPSdKO, showed two high molecular mass bands, between 242 and 480 kDa, both positive for PS1 and PS2, compatible with the previously described high molecular mass band (ϳ400 kDa) observed for fully assembled ␥-secretase (45, 70) (Fig.…”
Section: Expression Of Ps1 or Ps2 In Mefpsdko Cellsupporting
confidence: 83%
“…The fact that different amino acid substitutions on the same structural determinant result in opposite effects on PS activity while generally preserving the maturation of the complex suggests that the PS AXXXAXXXG motif could be important for the conformation of the mature ␥-secretase complex (70). Nondenaturating electrophoresis analyses were carried out (blue native PAGE), with HEK293 taken as a reference for the formation of the native ␥-secretase complex (70).…”
Section: Expression Of Ps1 or Ps2 In Mefpsdko Cellmentioning
confidence: 99%
“…This result suggests a γ-secretase component other than the catalytic presenilin is responsible for this selective cleavage function. Several EM structures of γ-secretase dating back as far as a decade have demonstrated that the ectodomain of nicastrin sits on top of the extracellular side of the γ-secretase TMDs (24,(49)(50)(51). It would therefore stand to reason that nicastrin itself might act to sterically block substrates with large ectodomains from entering the γ-secretase complex for catalysis.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics revealed here should be considered when studying the structure-function relationship of ␥-secretase complex (Lazarov et al, 2006;Osenkowski et al, 2009). …”
mentioning
confidence: 96%